Excitable Ras dynamics-based screens reveal RasGEFX is required for macropinocytosis and random cell migration - Koji Iwamoto; Satomi Matsuoka; Masahiro Ueda (Nature Communications)
Abstract Excitable systems of eukaryotic chemotaxis can generate asymmetric signals of Ras-GTP-enriched domains spontaneously to drive random cell migration without guidance cues. However, the molecules responsible for the spontaneous signal generation remain elusive. Here, we characterized RasGEFs encoded in Dictyostelium discoideum by live-cell imaging of the spatiotemporal dynamics of Ras-GTP and hierarchical clustering, finding that RasGEFX is primarily required for the spontaneous generation of Ras-GTP-enriched domains and is essential for random migration in combination with RasGEFB/M/U in starved cells, and they are dispensable for chemotaxis to chemoattractant cAMP. RasGEFX and RasGEFB that co-localize with Ras-GTP regulate the temporal periods and spatial sizes of the oscillatory Ras-GTP waves propagating along the membrane, respectively, and thus control the protrusions of motile cells differently, while RasGEFU and RasGEFM regulate adhesion and migration speed, respectively. Remarkably, RasGEFX is also important for Ras/PIP3-driven macropinocytosis in proliferating cells, but RasGEFB/M/U are not. These findings illustrate a specific and coordinated control of the cytoskeletal dynamics by multiple RasGEFs for spontaneous motility and macropinocytosis.